Strategy for Packaging Political Content on The Saeful Zaman Youtube Channel - Rita Herlina; Lisda Ariani Simabur; Fuji Fera Rahayu Ningsih; Andri Darmawan (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Many political events that Saeful Zaman Channel can discuss and criticize daily are the background of this research with the theme